1998
DOI: 10.1021/bi9728102
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of an Intramolecular DNA Triplex Linked by Hexakis(ethylene glycol) Units:  d(AGAGAGAA-(EG)6-TTCTCTCT-(EG)6-TCTCTCTT),

Abstract: A DNA molecule was designed and synthesized with three octanucleotide stretches linked by two hexakis(ethylene glycol) chains to form an intramolecular triplex in solution. The structural data obtained from a series of NMR NOESY spectra yielded interproton distances, and COSY experiments provided dihedral angle information for analysis of deoxyribose ring pucker. Using distance geometry followed by simulated annealing with restrained molecular dynamics and relaxation matrix refinement, a well-refined ensemble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
79
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 46 publications
10
79
0
Order By: Relevance
“…The ligands were built and optimized in MacroModel and the RESP charges were derived using ab initio calculations with 6–31G* basis set in Jaguar program [57]. The structure of the dA 10 .2dT 10 triplex was built starting from the experimental (NMR) solution structure of related DNA triplex [62,63]. Twenty seven sodium ions were added to neutralize the initial structure.…”
Section: Methodsmentioning
confidence: 99%
“…The ligands were built and optimized in MacroModel and the RESP charges were derived using ab initio calculations with 6–31G* basis set in Jaguar program [57]. The structure of the dA 10 .2dT 10 triplex was built starting from the experimental (NMR) solution structure of related DNA triplex [62,63]. Twenty seven sodium ions were added to neutralize the initial structure.…”
Section: Methodsmentioning
confidence: 99%
“…1c), so that the structural elements most essential in H-DNA formation are represented. Based on the present H-y5 structure and the structural data from H-y3 systems [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] , a mechanism is proposed for H-DNA formation consistent with the collective biochemical and biophysical data 2,3,9-13 . Fig.…”
mentioning
confidence: 75%
“…None of these theories could rely on direct conformational evidence, because all three-dimensional structures available were obtained for H-y3 type intramolecular triple helices [14][15][16][17][18][19][20][21][22][23] , containing limited data for their (triplex) loops and no data for the interaction of the latter with the purine strand extension. We present the complete solution structure of a DNA fragment that forms an intramolecular triple helix of the H-y5 type.…”
mentioning
confidence: 99%
“…In the literature there are few examples where EG6 was used in structural studies. To date, the spacer was used only in NMR studies showing a stabilization effect on the DNA duplexes and a triplex structure (3034). The NMR models revealed that EG6 did not interfere with the native DNA structure and showed conformational flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…The non-nucleotide spacers has been shown to increase the thermal stability of the structure of duplexes, triplexes or tetraplexes (2329). They were also implemented in nuclear magnetic resonance (NMR) (3034) and crystallographic studies (29,35,36) but so far such linkers has not been used to stabilize the native structure of RNA hairpins.…”
Section: Introductionmentioning
confidence: 99%